Enhancing Religious Moderation Among Interfaith Youth for Revitalizing Social Cohesion in Ilir Kota Village Sanggau Regency - Kurniawan, Syamsul; Fitriyanto, Andry (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2024)
The focus of this article is on enhancing religious moderation among interfaith youth to revitalize social cohesion in Ilir Kota Village, Sanggau Regency. This article is derived from community service activities based on research, employing the Participatory Action Research (PAR) method. The results indicate that the program to enhance religious moderation, focusing on revitalizing social cohesion in the Harmony-Conscious Village of Ilir Kota, demonstrates the practical implementation of Talcott Parsons' structural functionalism theory through the AGIL framework. Each element of AGIL—adaptation, goal attainment, integration, and latency—plays a crucial role in fostering a stable and harmonious society. Through various activities such as interfaith seminars, joint commitment declarations, social actions, and the establishment of communication forums, the program successfully created inclusive and sustainable patterns of social interaction.Fokus artikel ini adalah meningkatkan moderasi beragama di kalangan pemuda lintas agama untuk merevitalisasi kohesi sosial di Desa Ilir Kota, Kabupaten Sanggau. Artikel ini berasal dari kegiatan pengabdian kepada masyarakat berbasis penelitian dengan menggunakan metode Participatory Action Research (PAR). Hasilnya menunjukkan bahwa program peningkatan moderasi beragama yang berfokus pada revitalisasi kohesi sosial di Desa Sadar Kerukunan Ilir Kota mencerminkan penerapan praktis teori fungsionalisme struktural Talcott Parsons melalui kerangka AGIL. Setiap elemen AGIL—adaptasi, pencapaian tujuan, integrasi, dan pemeliharaan pola (latency)—memiliki peran penting dalam menciptakan masyarakat yang stabil dan harmonis. Melalui berbagai kegiatan seperti seminar lintas agama, deklarasi komitmen bersama, aksi sosial, dan pembentukan forum komunikasi, program ini berhasil menciptakan pola interaksi sosial yang inklusif dan berkelanjutan